2001
DOI: 10.1021/tx010042g
|View full text |Cite
|
Sign up to set email alerts
|

Imbalance of Estrogen Homeostasis in Kidney and Liver of Hamsters Treated with Estradiol:  Implications for Estrogen-Induced Initiation of Renal Tumors

Abstract: Reaction of endogenous catechol estrogen quinones (CE-Q) with DNA may initiate cancer by generation of oncogenic mutations. Treatment of male Syrian golden hamsters with estrogens or 4-catechol estrogens (4-CE), but not 2-CE, induces kidney, but not liver, tumors. The hamster provides an excellent model for studying activation and deactivation (protection) of estrogen metabolites in relation to formation of CE-Q. Several factors can unbalance estrogen homeostasis, thereby increasing the oxidative pathway leadi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
71
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 72 publications
(74 citation statements)
references
References 29 publications
3
71
0
Order By: Relevance
“…A number of findings support the concept that pregnancy-associated hormonal changes, and, particularly, high oestrogen levels, may promote malignant changes by stimulating renal cell proliferation either directly or via growth factors (Concolino et al, 1993). These findings include the fact that administration of potent oestrogens has been shown to induce renal cancers in the Syrian hamster (Kirkman, 1959;Reznik-Schuller, 1979;Li and Li, 1990;Cavalieri et al, 2001), the presence of oestrogen and progesterone receptors in normal and malignant renal cells (Concolino et al, 1976;Ronchi et al, 1984), and the observed association with obesity, which provides a major source of oestrogen in postmenopausal women. However, the evidence supporting a role of exposure to endogenous or exogenous oestrogens in renal cell carcinogenesis is conflicting.…”
Section: Discussionmentioning
confidence: 92%
“…A number of findings support the concept that pregnancy-associated hormonal changes, and, particularly, high oestrogen levels, may promote malignant changes by stimulating renal cell proliferation either directly or via growth factors (Concolino et al, 1993). These findings include the fact that administration of potent oestrogens has been shown to induce renal cancers in the Syrian hamster (Kirkman, 1959;Reznik-Schuller, 1979;Li and Li, 1990;Cavalieri et al, 2001), the presence of oestrogen and progesterone receptors in normal and malignant renal cells (Concolino et al, 1976;Ronchi et al, 1984), and the observed association with obesity, which provides a major source of oestrogen in postmenopausal women. However, the evidence supporting a role of exposure to endogenous or exogenous oestrogens in renal cell carcinogenesis is conflicting.…”
Section: Discussionmentioning
confidence: 92%
“…Experiments on estrogen metabolism [6][7][8][9][10], formation of DNA adducts [11][12][13][14][15][16][17], mutagenicity [17][18][19][20][21], cell transformation [22][23][24] and carcinogenicity [25][26][27][28] have led to the hypothesis that certain estrogen metabolites, predominantly catechol estrogen-3,4-quinones, react with DNA to cause the mutations leading to the initiation of cancer ( Fig. 1) [17].…”
Section: Introductionmentioning
confidence: 99%
“…Cytochrome P450 1A1 (CYP1A1) is involved in the conversion of estrone (E1) and estradiol (E2) to 2-hydroxyestradiol (2-OHE1) (Cavalieri et al, 2001). CYP1A1 also has aryl hydrocarbon hydroxylase activity which is responsible for metabolizing polycyclic aromatic hydrocarbons (PAH) to aryl epoxides (Law, 1990).…”
Section: Introductionmentioning
confidence: 99%